Peran Perangkat Desa Dalam Meningkatkan Kesejahteraan Masyarakat Muslim di Bidang Pertanian (Studi Kasus: Desa Gontor Kecamatan Mlarak Kabupaten Ponorogo Tahun 2017-2018) - Aqidah Halimatus Sa'adah; Arie Rachmad Soenjoto (Islamic Economics Journal, 2018)
The village is the forerunner to the formation of communities in Indonesia. One of the interesting phenomena on the life of the village are agricultural problems in the improvement of the welfare of the community. In addressing the issue of advancing, society will not be detached from the role of the village and the whole community of the village of Gontor. Because if the device partnership village with its community development eff orts in both the village and the improvement of the welfare of society, then the performance of the device can be said both villages. This research aims to know the role of Councilor in improving the welfare of the community in the fi eld of agriculture and to know the impact of the role of Councilor in improving the welfare of the community in the field of agriculture Gontor Subdistrict Mlarak Ponorogo years 2017-2018. By using descriptive qualitative approach, the results obtained from this research that States that the role of Councilor Gontor in improving the welfare of the community in the fi eld of agriculture which are giving examples of processing fi elds and doing agricultural extension as well as a Village-owned enterprises hard-wired from the Government for the prosperity of the village community. The impact of these roles is a society increasingly understand how to maximize agricultural output.